Palestine yesterday, today and tomorrow - Suwaidan, Tareq M. (Egedsa, 2006)
Since the dawn of history, the Palestinian issue has been the focal point of national and international conflicts in the Middle East. However, the historical realities of Palestine in general, and of Jerusalem in particular, have been manipulated, adulterated and even hijacked for one specific reason or another. The various accounts of events, taken out of their historical context and used for political, ethnic, religious and sectarian purposes, have spread confusion and uncertainty in contemporary culture, to such an extent that people today view the socio-historic situation of Palestine as fraught with insurmountable hurdles that prevent a correct understanding of the "Palestinian Problem". In the two years of lectures I have given on Palestine, I have verified that, by presenting history "from the outside looking in", in a logical, chronological sequence, one can gain a better understanding of historical realities, because it enables one to analyse historical facts reliably and impartially. By applying this methodology, I have rearranged the content of the abovementioned lectures in this book, so as to put within reach of the average reader a well-documented, and comparatively comprehensive treatise. This book contains two distinct parts-the first deals with the history of Jerusalem, from the dawn of time to well into the modern age; that is, up to the time of the Ottoman empire. In contrast, the second part focuses on demographic and political events from the fall of the Ottoman empire, and the subsequent colonial invasion, to the present time; in other words, from the end of the First World War to the death of Yasir Arafat in late 2004.